Reflections on the Indonesian Navy's Military Geostrategy Through Learning Against the Russian-Ukrainian War - Yosua Sabar Panjaitan; Lukman Yudho Prakoso; Buddy Suseto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Russian-Ukrainian war is the focus of the world's attention now. The existence of a war between these two countries has become a lesson for other countries in the world that war might occur in their country. This argument certainly applies to the Indonesian state. Through the Indonesian Navy, Indonesia has a vision of 5 Global Maritime Fulcrum. with a strategy to increase its war fleet and infrastructure. However, a war in Indonesia can still occur because war is not only due to a country's military strength but also its political factors. This study aims to evaluate the geostrategy of the Indonesian Navy's national army through its five pillars reflected in the Russia - Ukraine war. The method used in this research is descriptive evaluative using secondary data. The results of this study state that even though the Indonesian Navy has implemented the geostrategy of the five pillars of the Global Maritime Fulcrum, a war in Indonesia can still occur due to political factors. Political factors were the main cause of the Russia – Ukraine war, where Ukraine wanted to join NATO and endanger Russia. For this reason, the Indonesian government, including the Indonesian Navy, needs to emphasize solving political problems using a diplomatic approach.